4/11x-9+2/11x=18-3/11x

Simple and best practice solution for 4/11x-9+2/11x=18-3/11x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4/11x-9+2/11x=18-3/11x equation:


x in (-oo:+oo)

(4/11)*x+(2/11)*x-9 = 18-((3/11)*x) // - 18-((3/11)*x)

(4/11)*x+(2/11)*x+(3/11)*x-18-9 = 0

9/11*x-27 = 0 // + 27

9/11*x = 27 // : 9/11

x = 27/9/11

x = 33

x = 33

See similar equations:

| 1/2((100-y)-y)=40 | | 1/2(100-2x)=40 | | -3x^2+21x-18=0 | | .15x+.05(12-x)=.10(4) | | 11=((8x+7)/3) | | 0.5(x-(180-x))=50 | | 9n+56=7n-2n-4 | | 3x-4y=4+4 | | ((x+7)/14)=1-(3/2)x | | ((6n-5p)/11t)=c | | -7-9y=63 | | -7(7)+9y=-63 | | 184=.56x | | 74=.56x | | 1/5-1/12 | | y=-3/5(1)-6 | | 54=3y+9 | | 18-7y=108 | | y=3/5-6 | | 4x^2+3=-12x | | 2x-5(-10)=-10 | | 4n-7=33 | | x+5y=47 | | y=-8/9*1+8 | | x^2+258.86x+10.886=0 | | 19-2x/x=6-5/x | | (A+2)/6+(a-5)/3=(a-1)/12 | | 64m=-96 | | 48=3y+9 | | -56x+64y=-32 | | x+7=14-21x | | 36/(7*8-50+2*3)-45/(2*5+5) |

Equations solver categories